Positive Surgical Margin in Radical Retropubic Prostatectomy: Incidence and Prognostic Factors - S. B. Petrov (Onkourologiâ, 2006)
Increased incidence of radical prostatectomies in the treatment of patients with prostatic cancer (PC) necessitates analysis of causes of the disease relapses after surgery. Positive surgical margin (PSM) is considered as one of the main causes. Aim — study of the incidence of PSM in patients with a history of retropubic radical prostatectomy for clinically local and locally disseminated PC and evaluation of prognostic factors. The incidence of PSM was analyzed in 271 patients with a history of retropubic prostatectomy, with consideration for the preoperative level of PSA, tumor differentiation and dissemination; the efficiency of neoadjuvant therapy (NAT) for PSM reduction was evaluated. PSM was detected in 84 (31.0%) patients. Significant criteria for PSM prognosis are clinical stage of disease, Glisson sum, and relative number of positive biopsy columns. NAT significantly reduced the incidence of PSM only in patients with local PC. NAT is indicated for patients with clinical signs of extraprostatic extension. It is ineffective in patients with locally disseminated PC because it cannot change the incidence of PSM.